Biochar: An emerging policy arrangement in Brazil?. Issue 51 (August 2015) - Rittl, Tatiana Francischinelli; Arts, Bas; Kuyper, Thomas W.
Highlights: The Brazilian biochar debate is driven by Embrapa experts. The dominant ADE/biochar discourse has been replaced by biochar/technology discourse. The international biochar/climate change discourse hardly resonates in Brazil. Biochar topic is not covered by any formal procedure in Brazil so far. Abstract: Biochar, the solid product of pyrolysis, has emerged as a new technology and policy tool to address various environmental challenges (climate change, food production and agricultural waste management). The concept of biochar drew its inspiration from Amazonian practices that had led to the creation of Amazonian Dark Earth (ADE): fertile soils rich in (bio)char and human artefacts. In this article, we conceptualize biochar as an emerging policy arrangement, and examine it along the four dimensions of the Policy Arrangement Approach (PAA), which are actors, discourse, power and rules. We focus on Brazil as an important player in the international biochar debate. Our analysis shows that science experts are the predominant players in the network, while policy-makers, businessmen and farmers are marginally positioned. Experts from Embrapa occupy central positions and thus exercise most power in the network. Moreover, experts linked to ADE have lost prominence in the network. The reason for this is to be found in the shift from the ADE/biochar to the biochar/technology discourse. The latter discourse includes different coalitions such as 'climate change mitigation', the 'improvement of soil fertility' and 'improving crop residue management'. Although the biochar/climate coalition is dominant at the international level, it is far less prominent in Brazil. Nationally, it is particularly the discourses of 'improvement of soil fertility' and 'improving crop residue management' which have prompted actors' relationships and practices. However, the biochar/technology discourse has not (yet) been formally institutionalized in Brazil. As a consequence, the country lacks an established biochar policy field.